Perceptions of justice actors on juvenile fundamental rights and rehabilitation in Vietnam: findings from a multi-institutional survey - Chau, Hoang Xuan; Tuan, Hoang Minh; Nhung, Tran Thi Tuyet; Do, Ngoc Ha; Anh, Nguyen Chau; Nguyen, Thang The (Frontiers in Psychology, 2025)
This study explores the perceptions of justice and governance professionals in Vietnam regarding the protection of fundamental rights and the implementation of community-based reintegration measures for juvenile offenders. Drawing on a cross-sectional survey of 285 respondents—including police officers, prosecutors, legal aid providers, commune officials, and other local-level actors—the research investigates three key dimensions: the perceived objectives of juvenile justice, support for a specialized juvenile justice system, and the perceived necessity of 22 child-centered, community-based interventions aimed at rehabilitation and recidivism prevention. The findings reveal strong overall support for rehabilitative and educational goals over punitive approaches. A large majority of respondents endorsed the establishment of a dedicated juvenile justice system aligned with international standards, particularly the UN Convention on the Rights of the Child. Among the proposed interventions, those involving legal safeguards, psychological support, diversion, and family engagement received the highest levels of support. While perceptions were consistent across gender, education, and professional experience, differences emerged by occupational role, suggesting competing institutional logics. These insights offer critical input for aligning Vietnam’s juvenile justice reform efforts with child rights principles and global best practices.